SERIOUS NEWBORN DISEASES: REFLECTIVE STUDY - Evelly da Silva Olanda, Débora; Fernandes Filgueiras, Mateus; Thallyta Alexandre de Pontes, Arunna; Carolina Salustino dos Santos, Maria; Claudino do Nascimento, Nathalia; Allyson Gomes Ferreira, Jefferson; Costa Soares Silva, Talita; da Silva Caldas, Walissioneide (Health and Society, 2022)
This study was carried out with readings and group discussions, in the year 2022, so it is a study of the reflective modality. Among the main diseases that affect neonates capable of causing their death are prematurity, congenital malformations, cystic fibrosis, sickle cell anemia, organ failure, advanced or progressive cancer, severe cerebral palsy, severe trauma to the central nervous system, among some others. For situations in which the disease that afflicts the neonate does not have a cure causing pain and discomfort, the use of palliative actions has been identified to provide greater comfort and well-being.